Public health considerations for a potential Lyme disease vaccine in the United States: cost of illness, vaccine acceptability, and net costs of a vaccination program - Hook, Sarah A., author; Peel, Jennifer, advisor; Anderson, Brooke, committee member; Bayham, Jude, committee member; Magzamen, Sheryl, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.